2020
DOI: 10.1038/s41598-020-59239-1
|View full text |Cite
|
Sign up to set email alerts
|

Advanced tsunami detection and forecasting by radar on unconventional airborne observing platforms

Abstract: Sustaining an accurate, timely, and global tsunami forecast system remains a challenge for scientific communities. To this end, various viable geophysical monitoring devices have been deployed. However, it is difficult to implement new observation networks in other regions and maintaining the existing systems is costly. This study proposes a new and complementary approach to monitoring the tsunami using existing moving platforms. The proposed system consists of a radar altimeter, Global Navigation Satellite Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, the efficacy of the method relies on the spatial distribution of the observation points, which should not be a problem in our study area owing to the newly deployed seafloor observation network for earthquakes and tsunami along the Japan Trench (S‐net) (Kanazawa, 2013). Alternatively, for other regions, prospective tsunami observing systems utilizing commercial vessels (Mulia et al, 2017) and airplanes (Mulia et al, 2020) as observational platforms are also suitable for the data assimilation method. The combined modeling strategy could serve as a powerful tool for forecasting future tsunamis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of the method relies on the spatial distribution of the observation points, which should not be a problem in our study area owing to the newly deployed seafloor observation network for earthquakes and tsunami along the Japan Trench (S‐net) (Kanazawa, 2013). Alternatively, for other regions, prospective tsunami observing systems utilizing commercial vessels (Mulia et al, 2017) and airplanes (Mulia et al, 2020) as observational platforms are also suitable for the data assimilation method. The combined modeling strategy could serve as a powerful tool for forecasting future tsunamis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the tsunami source inversion (Sect. 2), the acquisition of various types of data has also contributed to improving the forecasting accuracy of tsunami data assimilation, including that from OBPGs, GPS buoys, and ship height positioning data of GNSS (Hossen et al, 2021;Mulia et al, 2017Mulia et al, , 2020a. Mulia et al (2017) conducted a synthetic experiment of tsunamis in the Nankai Trough, assimilating offshore tsunami data recorded in various observational systems.…”
Section: Improvement On Forecasting Accuracymentioning
confidence: 99%
“…(2015) first showed the possibility of the DA method for tsunami forecasting and in numerical experiments successfully applied it to a retrospective forecast of the 2011 Tohoku Earthquake tsunami. Subsequently, numerical experiments with the DA method have been applied to tsunami events with NOAA Deep‐Ocean Assessment and Reporting of Tsunamis (DART) sea‐floor pressure data, Cascadia Initiative sea‐floor pressure gauge data, ship‐borne Global Navigation Satellite System (GNSS) data, and airborne radar observations (e.g., Gusman et al., 2016; Maeda et al., 2015; Mulia et al., 2017, 2020; Sheehan et al., 2019; Wang et al., 2017). The DA method does not require precomputed Green's functions (GFs), though some studies have shown that precomputed GFs can reduce computation time for fixed observation sites (Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%